Pemecahan Saham Ditinjau dari Kinerja Keuangan dan Harga Saham: Bukti Empiris di Bursa Efek Indonesia - Nur, Dhani Ichsanuddin (Jurnal Aplikasi Manajemen, 2009)
Stock split solution is one of the capital restructure forms which was executed by a company caused split effect, that is a company execution which caused the rise of stock amount which spread proportionally more than the rise of company wealth. The research purpose is to analyze finance performance and the expensive share cost in the decision of stock split. Emitten which was included sample classified to two, namely one executed stock split in the term of January 2005 - December 2006 and one did not execute share solution on the term. The number of sample emitten is 13 emitten consisted of 6 emitten which executed stock split, have net profit data, earning per share (EPS), price to book value (PBV), and price to earning ratio (PER). Analysis device was ANOVA. The research result showed that there was no significant difference finance performance between company which executed share solution and company did not execute stock split, and no significant difference expensive share price between company which executed stock split and company which did not execute stock split.